Merjenje elektronskega poslovanja s pomočjo vzorčnih anket - Vehovar, Vasja (Uporabna informatika (Ljubljana), 1999)
The paper systematically discusses issues in survey measurement of electronic commerce. In particular, problems of definitions and sampling are adressed. The methodological problems are discussed also from a broader prospective of information society measurement. Empirical examples are presented from surveysperformed with the project RIS (Research on Internet in Slovenia) 1996-1999.
Keywords: ankete; elektronsko poslovanje; Internet; metode; raziskovanje; vzorčenje